Performance Analysis of Three Phase Cascaded H-Bridge Multilevel Inverter Design for Solar Power Plant Optimization - Widagdo, Reza Sarwo; Slamet, Puji; Hariadi, Balok (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
An inverter is an electrical device that converts direct current (DC) into alternating current (AC). Typically, a standard inverter operates at three voltage levels: +Vdc, -Vdc, and 0. However, a multilevel inverter consists of several smaller inverters connected in a series to produce multiple voltage levels at the output. The primary advantage of this type of inverter lies in its ability to produce a much lower harmonic distortion compared to traditional, non-multilevel inverters. Additionally, the switching components of a multilevel inverter operate at lower frequencies, which makes it more suitable for highpower applications. This research focuses on a threephase cascaded multilevel inverter, specifically generating output waveforms with up to seven levels. The study involves conducting experiments using RL loads, to observe how these variations affect the output waveforms and their harmonic distortions. The result, THDi values are much lower, with the 3rd harmonic contributing 0.02%, the 5th contributing 0.006%, the 7th contributing 0.004%, the 9th contributing 0.002%, the 11th contributing 0.002%, and the 13th harmonic contributing just 0.001%. These results suggest that the voltage harmonic more significant harmonic distortion than the current, particularly at the 13th harmonic order. This increase highlights the effect of inductive loads on the performance of the inverter, particularly in terms of harmonic content. These findings are crucial for optimizing multilevel inverters in practical applications, ensuring improved performance and efficiency.